Pendampingan Pembuatan Laporan Keuangan dan Pembayaran Berbasis Digital pada Toko Kue Kasippi Kabupaten Majene: Assistance in Making Digital-Based Financial Reports and Payments at Kasippi Cake Shop Majene Regency - Hasan, Asriani; Rizaldi, Andi Risfan; Hikmah, Hikmah (LP2M INSURI Ponorogo, 2023)
The use of QRIS has increased, but it differs from the 3T areas in Indonesia. One of the 3T areas is Majene Regency, located in West Sulawesi Province. Therefore, this Community Service activity (PKM) aims to assist in making financial reports and digital-based payments. The partner in this PKM activity is the Kasippi Mitra Sejahtera Cake Shop. Making a QRIS account in this activity uses the Bank Mandiri Livin'usaha application. For assistance in making financial reports using the Buku Warung application. The PAR (Participatory Action Research) method approach is the type of method used in this PKM activity. This activity consists of the problem identification stage, the preparation stage, the program implementation stage, and the evaluation stage. The results obtained in this PKM activity are that Digital Payments using QRIS make it easy for the public to make transactions. The results of this PKM also provide knowledge about making digital financial reports. Therefore, this assistance activity for creating financial statements and digital-based payments can positively impact partners, namely implementing digital costs on their businesses and recording and making simple financial reports using an application. This aims to make partners better at managing their business.